Pediatric Inflammatory Multisystem Syndrome Temporally Related With SARS-CoV-2: Immunological Similarities With Acute Rheumatic Fever and Toxic Shock Syndrome - Buonsenso, Danilo; Riitano, Francesca; Valentini, Piero (Frontiers in Pediatrics, 2020)
Several studies demonstrated that COVID-19 in children is a relatively mild disease. However, recently a more serious condition characterized by systemic inflammation with clinical or microbiological evidence of exposure to SARS-CoV-2 has been described. This syndrome is now known as either “Pediatric Inflammatory Multisystem Syndrome temporally related with COVID-19” (PIMS-TS) (6), or Multisystem Inflammatory Syndrome in Children (MIS-C) (7) and is currently considered a rare post-COVID-19 complication that, in a minority of cases, can lead to death. The presenting signs and symptoms are a mix of the ones for Kawasaki disease (KD) and toxic shock syndrome (TSS) and are characterised, by fever, systemic inflammation, abdominal pain and cardiac involvement. In this study, we describe clinical and immunological characteristics shared by PIMS-TS, ARF and TSS, in order to provide hypotheses to direct future clinical and basic research studies.